ESG Performance and Firm Size Drive Green Investment: The Mediating Role of Profitability - Puspaningtiyas, Itetasari; Fitriyah, Fitriyah (Publisher Cv. Inara, 2026)
The purpose of this study is to analyze the impact of ESG (Environmental, Social, and Governance) indicators and company size on green investment, with profitability as a mediating variable, in companies listed on the IDX ESG Index for the 2022-2024 period. Based on sustainable economic theory, companies must balance economic objectives with social and environmental responsibilities to achieve long-term growth. The approach used is quantitative, with an explanatory method utilizing secondary data in the form of annual reports, sustainability reports and ESG indicators. The research sample consisted of 70 companies selected by purposive sampling, and data analysis was conducted using path analysis based on panel data regression using Eviews. The results of this study are expected to show that ESG indicators and company size have a positive impact on profitability and green investment, with profitability mediating the relationship. These findings contribute to strengthening the green finance literature and provide practical implications for companies in optimizing economic sustainability strategies in Indonesia.